Determination of the Median Effective Dose (ED50) of Ciprofol for Successful Sedation in Pediatric Patients During General Anesthesia Induction - Nie P; Wu D; Du C; Wang X; Zhang H; Xiao H (Drug Design, Development and Therapy)
Peihe Nie,1 Di Wu,2 Chengjun Du,1 Xiaoqian Wang,1 Huan Zhang,1 Hongyi Xiao1 1Department of Anesthesiology, Weifang People’s Hospital, Weifang, 261041, People’s Republic of China; 2Department of Outpatient, Weifang People’s Hospital, Weifang, 261041, People’s Republic of ChinaCorrespondence: Hongyi Xiao, Department of Anesthesiology, Weifang People’s Hospital, Weifang, 261041, People’s Republic of China, Email 1185549168@qq.comPurpose: To determine the median effective dose (ED50) and 90% effective dose (ED90) of ciprofol for successful sedation during general anesthesia induction in pediatric patients, optimize dosing regimens, and provide reference evidence for clinical practice.Patients and Methods: We enrolled pediatric patients aged 3– 12 years scheduled for elective surgery under general anesthesia with endotracheal intubation. The first patient received intravenous ciprofol 0.4 mg/kg. Using the modified Dixon’s up-and-down sequential method, the ciprofol dose for each subsequent patient was determined based on the previous patient’s sedation response. Sedation success was evaluated using two clinical endpoints: loss of eyelash reflex (LER) and acceptance of facemask (AFM). We calculated the ED50, ED90 and their 95% confidence intervals (CI) of ciprofol for successful induction sedation. Secondary outcomes included eyelash reflex disappearance time, vital sign changes during induction, and adverse events.Results: The study achieved 7 transition points (from sedation success to failure) with a total enrollment of 36 pediatric cases. The ED50 and ED90 (with 95% CI) of ciprofol for successful induction sedation in pediatric general anesthesia were 0.618 (0.576~0.666) mg/kg and 0.708 (0.661~0.916) mg/kg, respectively. Eyelash reflex disappearance occurred at 31.04± 8.19 seconds post-induction. During anesthesia induction, one case of hypoxemia was observed, while no patients experienced injection pain or hypotension.Conclusion: Ciprofol demonstrates efficacy for anesthesia induction in pediatric patients aged 3– 12 years. In the absence of premedication, the median effective dose (ED50) of ciprofol for successful sedation during general anesthesia induction in pediatric patients was 0.618 mg/kg. The recommended dose of ciprofol for induction of general anesthesia in children 3– 12 years of age is 0.6– 0.7 mg/kg to ensure smooth passage through the mask-assisted respiration phase during induction.Keywords: ciprofol, effective dose, pediatric, anesthesia, general